SOCIALLY RESPONSIBLE HUMAN RESOURCE MANAGEMENT DAN CSR BEHAVIOUR TERHADAP ORGANIZATIONAL TRUST SAAT PANDEMI COVID-19 - Hurian Kamela; Ryan Saputra Alam (Universitas Islam Negeri Alauddin Makassar, 2021)
Socially Responsible Human Resource Management (SRHRM) and CSR Behavior are factors that play a role in measuring the condition of employees working in a company environment, especially in management organizations. The purpose of this study is to quantitatively analyze SRHRM and CSR Behavior on Organizational Trust. The goal is to find out the condition of employees when facing the COVID-19 pandemic so that their effectiveness and efficiency can be measured. The data uses primary data (questionnaire). The total sample is 64 private companies in Greater Jakarta for the 3 months period of COVID-19 (May-June-July 2021). The reason the sample was taken is that private companies in Jabodetabek have an average CSR and effective organization so that the influence of their employees can be measured. The research method uses linear regression with STATA. The dependent variable is Organizational Trust 5 items: fairness, commitment, promise, management, career development. The independent variables are SRHRM and CSR Behavior based on the questionnaire items. The results of the study explain that SRHRM affects Organizational Trust. SRHRM creates a conducive work environment so that trust increases because the organization is effective. While other results, CSR Behavior does not affect Organizational Trust, due to differences of opinion between employees and the company, because companies affected by the pandemic do not allow companies to develop their employees' CSR Behavior strategies.